2021
DOI: 10.1155/2021/6639612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sugar Beet Harvest Date on Its Technological Quality Parameters by Exploratory Analysis

Abstract: Choice of the harvest date is one of the foundations of vintage quality and good-yield sugar in sugar beet. However, it is difficult to define the harvest date and more precisely the date of maturity of beet roots, in an exact and absolute way. Indeed, maturity is divided into several stages and degrees depending on environmental and climatic conditions such as temperature, precipitation, geographic area, and others. The present study evoked the effect of three harvest dates (at esteemed maturity, 7 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…such effect may be due to delaying beet harvest allow to increase growth period and photosynthesis of sugar beet plants which led to an increase in root and sugar yields (ton/fed.). These results are harmony with those obtained by Abd El-Razek and Ghonema (2016), Nagib et al (2018) and Lamiae et al (2021).…”
Section: Influence Of Harvesting Dates On Yield and Quality 311 Influ...supporting
confidence: 91%
See 1 more Smart Citation
“…such effect may be due to delaying beet harvest allow to increase growth period and photosynthesis of sugar beet plants which led to an increase in root and sugar yields (ton/fed.). These results are harmony with those obtained by Abd El-Razek and Ghonema (2016), Nagib et al (2018) and Lamiae et al (2021).…”
Section: Influence Of Harvesting Dates On Yield and Quality 311 Influ...supporting
confidence: 91%
“…Beets harvested at older age (210 days after sowing) surpassed those harvested earlier (180 days after sowing) in all traits in both seasons, except loss in sugar yield/fed., purity % and α-amino-N%. Lamiae et al (2021) cleared that the suitable harvest date is one of the most important factors for a good sugar yield and quality of sugar beet. Sugar beet seeds sown in Egypt were imported from foreign countries and had large differences in gene make-up expression in its root yield and quality characteristics, therefor it well be tested annually under Egypt conditions to obtained the best varieties in yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that PC1 can be referred to as the high-root weight component and the basis in the weighting of selection genotypes, thus PC1 is important to increase sugar beet productivity in the three environments. Alami et al [23], Islam et al [24], Majumdar et al [26] and Mehareb et al [40] have previously revealed similar results for the first two main PCs.…”
Section: Which-won-where Patternmentioning
confidence: 65%
“…[22], Alami et al [23], Islam et al [24], Kleuker and Hoffmann [25] and Majumdar et al [26]. The aim of this work was to study the effect of environment on genotypes of sugar beet under various regions in Egypt, and evaluate the magnitude of genotype x environment interaction using the multivariate methods, thus discovering the most stable sugar beet genotype and determining associations for the studied traits in ten sugar beet genotypes under three different environments.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive amounts of these elements, deficiencies or disturbances in their correct proportions in the soil lead to abnormalities in the development of sugar beet plants and to a reduction in the amount of sugar produced and deterioration of its quality, mainly due to the formation of molasses [9][10][11][12][13][14][15][16]. The correct date of sowing [17] and harvesting [18] also determines the success of the size and quality of the crop.…”
Section: Introductionmentioning
confidence: 99%